2015
DOI: 10.1155/2015/286137
|View full text |Cite
|
Sign up to set email alerts
|

Bacoside A: Role in Cigarette Smoking Induced Changes in Brain

Abstract: Cigarette smoking (CS) is a major health hazard that exerts diverse physiologic and biochemical effects mediated by the components present and generated during smoking. Recent experimental studies have shown predisposition to several biological consequences from both active and passive cigarette smoke exposure. In particular, passive smoking is linked to a number of adverse health effects which are equally harmful as active smoking. A pragmatic approach should be considered for designing a pharmacological inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 172 publications
(166 reference statements)
0
12
0
Order By: Relevance
“…It is well known that cigarette smoking is an intractable and preventable public health problem. 67 Many previous studies 26,50,56,63,66,68,69 have explored the role of smoking in OAB. Although some studies 26,69 found no relationship between smoking and OAB, other studies 50,63 reported that smoking was a risk factor for the onset of OAB.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that cigarette smoking is an intractable and preventable public health problem. 67 Many previous studies 26,50,56,63,66,68,69 have explored the role of smoking in OAB. Although some studies 26,69 found no relationship between smoking and OAB, other studies 50,63 reported that smoking was a risk factor for the onset of OAB.…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic imbalance is not just associated with cardiovascular disease, but with myriad CNS disorders such as Parkinson's Disease (Haapaniemi et al, 2001), Fragile X syndrome (Boccia and Roberts, 2000), and depression (Agelink et al, 2001). Furthermore, recent studies suggested that air pollution, including SHS, is linked to CNS disorders and neurodegenerative diseases (Calderon-Garciduenas et al, 2015;Vani et al, 2015;Kim et al, 2020;Shabani, 2021). Reducing SHS exposure in non-smokers with smoke-free policies in public venues could have a broader benefit to public health beyond pulmonary and cardiovascular consequences.…”
Section: Perspectivementioning
confidence: 99%
“…Besides, Vani et al. (2015) reported increased Purkinje cells and activated microglia and astrocytes in neural parenchyma of CS‐exposed rats. In the present study, citalopram showed protective influence with mild neural congestion.…”
Section: Discussionmentioning
confidence: 99%